Efektivitas Relaksasi Benson dan Hipnosis Lima Jari Terhadap Penurunan Tingkat Kecemasan Pasien Preoperasi Sectio Caesaria - Surtiningsih Surtiningsih; Iin Handayani; Silvia Rizki Syah Putri (SEHATI: Jurnal Kesehatan, 2026)
A Caesarean section (CS) involves a surgical process for delivering a baby, which often triggers fear and pain, leading to anxiety. If not managed effectively, this anxiety can negatively impact both the mother and the baby. As non-pharmacological alternatives to managing anxiety, Benson relaxation therapy and five-finger hypnosis have shown promise. This study aims to evaluate the effectiveness of Benson relaxation therapy and five-finger hypnosis in reducing anxiety levels among pre-operative Caesarean section patients. A quasi-experimental design with a two-group pretest-posttest approach was employed. The study sample comprised 60 Caesarean section patients at the Regional General Hospital, selected through purposive sampling. The STAI-S questionnaire was used as the research instrument, and data were analyzed using Wilcoxon and Mann-Whitney tests. The findings revealed a significant reduction in anxiety levels in pre-operative Caesarean section patients after receiving Benson relaxation therapy (p-value 0.000) and five-finger hypnosis (p-value 0.000). Additionally, a notable difference in anxiety levels was observed between the Benson therapy group and the five-finger hypnosis, with a p-value of 0.011